Borrowing without debt? Understanding the US international investment position - Matthew Higgins; Thomas Klitgaard; Cédric Tille (Federal Reserve Bank of New York, 2006)
Sustained large U.S. current account deficits have led some economists and policymakers to worry that future current account adjustment could occur through a sudden and disruptive depreciation of the dollar and a sharp drop in U.S. consumption. Two factors that, to date, have cast doubt on such concerns are the stability of U.S. net external liabilities and the minimal net income payments made by the United States on these liabilities. We show that the stability of the external position reflects sizable capital gains stemming from strong foreign equity markets and a weaker dollar—conditions that could be reversed in the future. We also show that while minimal U.S. net income payments reflect a much higher measured rate of return on U.S. foreign direct investment (FDI) assets than on U.S. FDI liabilities, ongoing borrowing is likely to overwhelm this favorable rate of return, pushing the U.S. net income balance more deeply into deficit. In addition, we review the argument that the United States holds large amounts of intangible assets not captured in the data—assets that would bring the true U.S. net investment position close to balance. We argue that intangible capital, while a relevant dimension of economic analysis, is unlikely to be substantial enough to alter the U.S. net liability position.
Keywords: F32; F34; F36; F41; 330; current account deficit; valuation effect; intangible capital; Zahlungsbilanzungleichgewicht; Abwertung; Immaterielles Anlagevermögen; Direktinvestition; USA